EDUCATION AND TRAINING An audible patient voice: How can we ensure that patients are treated as partners in their own safety?. Issue 3 (2021) - Subbe, Christian P; Ahsan, Saleyha; Smith, Lowri; Renggli, Johanna Frey
No abstract available